Branchlet shaking: a method for sampling tree canopyarthropods under windy conditions - Majer, Jonathan; Recher, H.; Keals, N. (1996)
Chemical knockdown is a commonly used method for sampling canopy arthropods. The procedure is susceptible to high winds and in certain conditions may be virtually unusable. Here we introduce a new procedure, branchlet shaking, and compare it with chemical knockdown. Samples produced by branchlet shaking yield fewer arthropods per tree and tend to miss some larger (>l.Ocm) and some smaller (<O.2cm) animals. However, the two procedures generally produce data which can portray similar information about the canopy fauna. It is concluded that although chemical knockdown is a superior sampling procedure, branchlet shaking is a possible alternative for situations where chemical knockdown is impractical. Interpretation of the data must, however, take into account the limitations of the branchlet shaking procedure.